Characteristics of Future Warmer Base States in CESM2. Issue 9 (18th September 2020) - Meehl, Gerald A.; Arblaster, Julie M.; Bates, Susan; Richter, Jadwiga H.; Tebaldi, Claudia; Gettelman, Andrew; Medeiros, Brian; Bacmeister, Julio; DeRepentigny, Patricia; Rosenbloom, Nan; Shields, Christine; Hu, Aixue; et al.
Abstract: Simulations of 21st century climate with Community Earth System Model version 2 (CESM2) using the standard atmosphere (CAM6), denoted CESM2(CAM6), and the latest generation of the Whole Atmosphere Community Climate Model (WACCM6), denoted CESM2(WACCM6), are presented, and a survey of general results is described. The equilibrium climate sensitivity (ECS) of CESM2(CAM6) is 5.3°C, and CESM2(WACCM6) is 4.8°C, while the transient climate response (TCR) is 2.1°C in CESM2(CAM6) and 2.0°C in CESM2(WACCM6). Thus, these two CESM2 model versions have higher values of ECS than the previous generation of model, the CESM (CAM5) (hereafter CESM1), that had an ECS of 4.1°C, though the CESM2 versions have lower values of TCR compared to the CESM1 with a somewhat higher value of 2.3°C. All model versions produce credible simulations of the time evolution of historical global surface temperature. The higher ECS values for the CESM2 versions are reflected in higher values of global surface temperature increase by 2, 100 in CESM2(CAM6) and CESM2(WACCM6) compared to CESM1 between comparable emission scenarios for the high forcing scenario. Future warming among CESM2 model versions and scenarios diverges around 2050. The larger values of TCR and ECS in CESM2(CAM6) compared to CESM1 are manifested by greater warming in the tropics. Associated with a higher climate sensitivity, for CESM2(CAM6) the first instance of an ice‐free Arctic in September occurs for all scenarios and ensemble members in the 2030–2050 time frame, but about a decade later in CESM2(WACCM6), occurring around 2040–2060. Plain Language Summary: The new Earth system model versions CESM2(CAM6) and CESM2(WACCM6) have higher equilibrium climate sensitivity than the previous model version CESM1. While this higher climate sensitivity produces greater warming by the end of the 21st century in CESM2(CAM6) and CESM2(WACCM6) compared to CESM1 for the high forcing scenario, prior to midcentury the warming is comparable among all model versions and scenarios. The higher climate sensitivity in CESM2(CAM6) and CESM2(WACCM6) compared to CESM1 produces greater tropical warming and precipitation increases in those regions. CESM2(CAM6) does not warm as much in the tropics as CESM2(WACCM6), though CESM2(CAM6) shows the first instance of an ice‐free Arctic in September for all scenarios and ensemble members about a decade earlier than in CESM2(WACCM6). Key Points: CESM2(CAM6) and CESM2(WACCM6) have higher equilibrium climate sensitivity (ECS) but about the same transient climate response (TCR) compared to CESM1 Future global warming diverges around 2050, with greater warming by end of century in the higher forcing scenarios and in both versions of CESM2 compared to CESM1 There is more future warming (and greater precipitation increase) in the tropics in the CESM2 versions compared to CESM